ANTIOXIDANT ACTIVITY DETERMINATION IN A LIPIDIC PEROXIDATION MODEL OF BUTTER INHIBITED BY ISOESPINTANOL - ROJANO, Benjamín A.; GAVIRIA, Carlos A.; SÁEZ, Jairo A. (Vitae, 2009)
The antioxidant activity (Φ) is defined as the slope of the simple linear regression of φ0/φi against the concentration μM, in an inhibition model of lipid peroxidation of butter at 60° C, where φi is the concentration effect of isoespintanol and φ0 is the control. It is found that the formation of: hydroperoxides (peroxide value of PV) and the most oxidized species reactive to thiobarbituric acid (TBARS), were similarly delayed by isoespintanol (ΦTBARS = 9.46x10-5 ± 1.33x10-5 and ΦPV = 9.41x10-5 ± 1.62x10-5). Likewise, the butilhidroxy toluene and isoespintanol inhibit the oxidative process of butter in a 28.0 and 23.3% at concentrations of 2380.9 and 3809.5 μ M respectively.